Technology: nursing the system. A new millennium for health care IT: the year 2000 conversion. - Simpson RL (Nursing Management)
The new millennium. It means many things for many people, from astrologers to information technology (IT) professionals. But the latter, especially those in health care, have good reason to be concerned. Because for the majority of computer systems, January 1,2000, marks both the beginning of a new decade and total system chaos.